2005
DOI: 10.1002/mus.20430
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory evoked potential and clinical changes after electrode implant in basal ganglia of parkinsonian patients

Abstract: Median nerve somatosensory evoked potentials (SEPs) were recorded in three parkinsonian patients who underwent electrode implant in the subthalamic nucleus and/or globus pallidus for chronic deep brain stimulation (DBS). SEPs were evoked before surgery, in a medication-free condition, and after the functional stereotactic procedure, before beginning DBS. In order to evaluate the timing of the SEP changes after the electrode implant, in three further patients SEPs were recorded within the operating theater, bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
0
9
1
Order By: Relevance
“…Existing somatosensory‐evoked potential (SEP) results have presented both an increase and decrease in early cortical deflections in amplitude by DBS [Insola et al,2005; Pierantozzi et al,1999; Priori et al,2001]. The present results display no significant difference between the DBS on/off conditions at the group level.…”
Section: Discussioncontrasting
confidence: 62%
“…Existing somatosensory‐evoked potential (SEP) results have presented both an increase and decrease in early cortical deflections in amplitude by DBS [Insola et al,2005; Pierantozzi et al,1999; Priori et al,2001]. The present results display no significant difference between the DBS on/off conditions at the group level.…”
Section: Discussioncontrasting
confidence: 62%
“…It has been reported that decreased amplitude of the frontocentral N30 component of the median nerve SEPs in PD patients can be restored by dopaminergic medications34, 35 or after DBS electrode implantation in the internal globus pallidus or the STN without turning on the stimulation,36 likely due to a microlesion effect. We found no change in the SEP amplitudes or latencies from the PPNR after administration of dopaminergic medications, suggesting that changes in SEP associated with dopaminergic medications likely occur rostral to the PPNR.…”
Section: Discussionmentioning
confidence: 99%
“…In OCD patients, it was used to study the role of the associative-limbic STN on the cortical networks of motor inhibition during a stop signal task (Kibleur et al 2016). The same methodology was also used to study ERPs amplitude and latency modulation by DBS on visual evoked potentials (Jech et al 2006;Priori et al 2001), in a passive rhythmic auditory stimulation task (Gulberti et al 2015b), in a working memory task (Selzler et al 2013) and in an auditory Go/NoGo task in PD patients stimulated in the STN (Gerschlager et al 1999; and on SEPs in PD patients with STN (Priori et al 2001;Conte et al 2010;Insola et al 2005) and GPi DBS (Pierantozzi et al 1999). As for SCEPs, the reconstruction of ERP sources, for example using minimum norm (Kibleur et al 2016) or multiple sparse priors (Kibleur et al 2017), can help defining the projection of DBS modulation on cortical regions activated by the specific cognitive tasks.…”
Section: Task-related Evoked Responsesmentioning
confidence: 99%